Factors Affecting Accounting Conservatism with Litigation Risk as a Moderator in Consumer Non- Cyclicals Companies Listed on IDX - Kinaryosih, Nimas Caesar Ratu; Budiwitjaksono, Gideon Setyo; Wilasittha, Acynthia Ayu (Universitas Ibn Khladun Bogor, 2024)
This study aims to examine the effect of information asymmetry and income smoothing on accounting conservatism moderated by litigation risk. The research uses a quantitative approach. The population in this study includes all consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. The purposive sampling method was used in determining the sample in this study and the financial statement reports of 140 companies are selected. Partial Least Square (PLS) was used as the analytical technique. The results showed that information asymmetry affects accounting conservatism and income smoothing does not affect accounting conservatism. This study also uses litigation risk as a moderator which found that litigation risk can moderate the effect of information asymmetry on accounting conservatism but unable to moderate the effect of income smoothing on accounting conservatism.